Efeitos do tratamento com cromoglicato dissódico nas alterações morfofuncionais associadas ao início da nefropatia diabética experimental - Luz, Mateus Jacinto da (2021)
Mast cells have antifibrotic and pro-fibrotic actions and appear to contribute to the development of diabetic nephropathy (DN). Despite the role of some possible mast cell mediators in the pathogenesis of DN has been proposed, little is known about the cellular mechanisms involved in the process, mainly those concerning type I and III collagen deposition in the renal parenchyma. Therefore, we evaluated the effect of disodium cromoglycate (CG) treatment, a drug that inhibits mast cell degranulation, on the morphofunctional parameters of kidneys from rats with experimental diabetes mellitus (DM) induced by the administration of alloxan (50 mg/kg, i.v.). Control or diabetic animals (blood glucose> 200 mg/dl) were treated or not with CR (50 mg/kg/day, i.p., from the 7th day after DM induction until 95th day). Urinary albumin excretion (UAE) and glomerular filtration rate (GFR) were assessed on the 90th day. After systolic blood pressure (SBP) measurement, kidneys were collected from anesthetized animals on the 95th day. Kidney slides stained with toluidine blue or picrosirius red were subjected to morphological analysis or immunohistochemistry to detect α-smooth muscle actin (α-SMA) or proliferating cell nuclear antigen (PCNA). Renal mast cell density and activity, renal corpuscle and tuft glomerular area, kidney weight/body weight ratio, renal interstitial collagen deposition (type III, and the sum of type I with type III collagen), UAE, and tubulointerstitial PCNA expression were increased in diabetic animals. Despite DM decreased GFR, neither renal α-SMA expression nor SBP were altered by the disease. The alteration in renal mast cell density and activity, renal corpuscle area, kidney weight/body weight ratio, renal interstitial collagen deposition and GFR were partially reversed by CG treatment. Glomerular tuft area and tubulointerstitial PCNA expression were normalized by CG treatment, while UAE, SBP and renal α-SMA expression did not change. These data suggest that the increases in the density and activity of mast cells within the kidney in the early stages of DN contribute to tubulointerstitial collagen deposition even in the absence of alterations in the renal myofibroblast population. CG treatment showed renoprotective effects in diabetic rats which appears to be related to its mast cell stabilizing property and to its ability to prevent some detrimental morphofunctional alterations.